De Novo Genotypic Heterogeneity in the UL56 Region in Cytomegalovirus-Infected Tissues: Implications for Primary Letermovir Resistance. (5th December 2019) - Jo, Horim; Kwon, Da Eun; Han, Sang Hoon; Min, Seo Yeon; Hong, Yeon-Mi; Lim, Beom Jin; Lee, Kyoung Hwa; Jo, Jeong-Hyeon
Abstract: Background: Letermovir, an inhibitor of unique long ( UL ) 56 -encoded cytomegalovirus (CMV)-terminase, shows prophylactic effects with low-grade adverse events in hematopoietic stem cell transplant recipients. Despite few case reports on acquired letermovir resistance, the frequency of de novo amino acid (A.A.) changes encoded by UL56 in CMV-infected tissues is unclear. Methods: We analyzed CMV UL56 sequences between the conserved region IV and variable region I in 175 formalin-fixed, paraffin-embedded tissues obtained from 147 patients showing positive CMV immunochemical staining between November 2012 and October 2016. Nucleotides 552–1330 of the open reading frame of UL56 were amplified with 5 primers and sequenced by a dideoxy fluorescence-based cycle. Results: Six (3.4%) tissues from 4 (2.7%) patients harbored A.A. substitutions. There were no known potent resistant mutations. However, we found C325Y in 2 tissues from 1 patient, along with other mutations. Four novel A.A. changes, which have not been observed in previous in vitro experiments, were identified (T244I, S301T, G312V, and M434I). Most (9 of 11, 81.8%) of the A.A. changes occurred between the codons 301 and 325 present between the conserved regions V and VI. Conclusions: The treatment difficulties associated with letermovir resistance in a clinical setting need to be verified before its widespread use. Abstract : There were some primary mutations leading to amino acid changes including C325Y in the UL56 region of CMV-infected tissues. The resistance barrier of letermovir in a clinical setting needs to be verified before its therapeutic use.